Traffic offences detector / Nor Shamira Shahnun, Qamarina Ahmad Suhaimi and Nur Aznida Azmani - Shahnun, Nor Shamira; Ahmad Suhaimi, Qamarina; Azmani, Nur Aznida (2017)
In Malaysia, the accident including fatal accident involving big vehicles increasing in time. Nowadays, due to urbanization people who are living in a fast-pace lifestyle, people tend to be selfish and forget about others when driving in order to arrive faster at the destination. Therefore, Mulan Enterprise will take this opportunity to offer a Traffic Offences Detector to reckless drivers. This device can detect and remind the driver about traffic offences that they had done intentionally or accidentally and advise them the right way of driving so that they will always realize and not repeat the same mistakes. Our Traffic Offences Detector will be introduced to drivers who driving big vehicles such as motorcars, busses and lorries. This detector may enter the market as 94% drivers from the concept testing like and would buy the product. The market survey done on 50 drivers in Shah Alam as 90% of them shows interest toward this product. In Malaysia, the accident including fatal accident involving big vehicles increasing in time. Nowadays, due to urbanization people who are living in a fast-pace lifestyle, people tend to be selfish and forget about others when driving in order to arrive faster at the destination. Therefore, Mulan Enterprise will take this opportunity to offer a Traffic Offences Detector to reckless drivers. This device can detect and remind the driver about traffic offences that they had done intentionally or accidentally and advise them the right way of driving so that they will always realize and not repeat the same mistakes. Our Traffic Offences Detector will be introduced to drivers who driving big vehicles such as motorcars, busses and lorries. This detector may enter the market as 94% drivers from the concept testing like and would buy the product. The market survey done on 50 drivers in Shah Alam as 90% of them shows interest toward this product.